تصور مقترح لاستخدام التعليم الإلكتروني في تعليم اللغة العربية وتعلمها بالتعليم العام في ليبيا (Journal of Academic Research, 2024)
This research aimed to present a proposed vision for using e-learning in teaching and learning the Arabic language in public education in Libya. The research problem was to formulate this goal into a question: Given that this research is of the type of analytical theoretical research; The researcher used the descriptive analytical, inductive, and deductive method, and the limits of the research were the objective limit: which is the proposed vision for using e-learning in teaching and learning the Arabic language, and the spatial limit: public education in Libya.In designing his proposed vision, the researcher relied on the systems analysis method (inputs - processes - outputs - feedback), and the researcher reached some results, including: the possibility of implementing the proposed vision by Arabic language teachers to benefit from the advantages of e-learning in improving the quality of public education in Libya, and recommends The researcher implemented this proposed concept and tested it with teachers in classrooms if electronic devices were available in schools. And provide their comments about it to develop and improve it in the future. The researcher proposes to conduct research and field and experimental studies on e-learning in the field of the Arabic language, and to benefit from their results.